2019
DOI: 10.1093/nop/npz003
|View full text |Cite
|
Sign up to set email alerts
|

Current state of clinical trials in breast cancer brain metastases

Abstract: Background Breast cancer brain metastases (BCBM) are the final frontier in neuro-oncology for which more efficacious therapies are required. In this work, we explore clinical trials in BCBM, and determine the shortcomings in the development of new BCBM therapies to shed light on potential areas for enhancement. Methods On July 9, 2018, we searched ClinicalTrials.gov for all interventional and therapeutic clinical trials invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…In addition, the exclusion of patients with metastasis from clinical trials prevented faster progress. 223 However, advancements in the field have changed the reigning paradigm and offered hope for future success. A photoacoustic method for direct use in patients with melanoma has been developed, allowing for the detection of very low numbers of CTCs in vivo and their subsequent destruction with laser pulses.…”
Section: How Does the Release Of Chemokines And Cytokines Help Circulmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the exclusion of patients with metastasis from clinical trials prevented faster progress. 223 However, advancements in the field have changed the reigning paradigm and offered hope for future success. A photoacoustic method for direct use in patients with melanoma has been developed, allowing for the detection of very low numbers of CTCs in vivo and their subsequent destruction with laser pulses.…”
Section: How Does the Release Of Chemokines And Cytokines Help Circulmentioning
confidence: 99%
“…Major obstacles lie in the lack of clinical trials that target metastasis and the lack of knowledge of the biological underpinnings that govern the metastatic process. 169,171,220,223 Designing targeted therapies for metastatic cancer cells should take into account the genetic and phenotypic differences between parental and metastatic/circulating cells. 294 Today, the diagnosis of metastatic cancer continues to be associated with a terminal label.…”
Section: Colonizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Lebanon, health communication studies mostly focused on three major health problems that the nationals in the country deal with: cancer, smoking and the refugee crisis. Promoting cancer awareness and establishing treatment guidelines were the focus of two health communication papers,10 11 especially after the rise in the number of cancer cases in the past decade 12–15. Another study explored the role of religion in dictating smoking behaviour in the country 16.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, overall research regarding the treatment of BCBM patients have not been rigorous. Fares et al identified several factors impeding the BCBM research such as low number of trials, low accrual numbers, and lack of diversity (96). In addition, these hurdles would also need to be overcome through proper selection of treatment regimens to be investigated.…”
Section: Future Perspectivementioning
confidence: 99%